Effect of Propofol and Isoflurane on Hemodynamic changes during Spinal Surgery Under General Anesthesia (East West Medical College Journal, 2024)
Background: Hemodynamic stability are vital requirements of up-to-date anesthesia. Both propofol and isoflurane meet these criteria though the clinical effects like postoperative nausea vomiting after administering propofol and isoflurane have been studied in various surgeries but have not been much evaluated or studied in patients undergoing major surgical procedures like spine surgeries, There’ is definite advantage of one technique over the other. Isoflurane has a low blood gas partition coefficient, which contributes to rapid induction and emergence from anaesthesia than with other volatile anesthetics in current clinical use. Propofol has been established as the intravenous agent that provides faster and smoother recovery & peri operative hemodynamic stability. Objective: To compare the effects of isoflurane and propofol regarding hemodynamic status in spinal surgery under general anaesthesia. Methods: After getting ethical approval, a randomized controlled trial study design was performed where patients were selected in the pre-anesthetic checkup room based on inclusion and exclusion criteria for those who were scheduled for spine surgeries under general anesthesia is admitted in the Department of Neurosurgery in East West Medical College from January 2023 – December 2024. A total number of 40 patients were selected. 20 patients were enrolled each in group A and group B by lottery method in a sealed envelope. They were divided into two groups by randomization; Group A and Group B. A written informed consent was taken from all selected patients. Patients were advised to fast for at least 8 hours before intervention. In Group A, anesthesia is maintained with propofol infusion, nitrous oxide (66%), and oxygen (33%) while in Group B, anesthesia is maintained with Isoflurane, nitrous oxide (66%), and oxygen (33%). All patients were given N2O in oxygen and 1.25% inspired concentration of Isoflurane (MAC -1.15). In Group A propofol infusion at rate of 80 μg/kg/min (fixed from the beginning). All data was collected at –Just after starting, 15 minutes, 30-minute, 1 hour, and >1 hour interval per operatively. Data was compiled, edited and plotted in tabular and figure form. P value was determined as significant when it was 0.05). Similarly, mean DBP was also higher in Group B than Group A (p = >0.05). Conclusion: Propofol is better for maintaining hemodynamic status than Isoflurane for Spine surgery under General anaesthesia.EWMCJ Vol. 12, No. 1&2, January-July 2024: 21-26